Kiprah Macandahan Memberdayakan Literasi Pemuda untuk Mewujudkan Pembangunan Berkelanjutan - Eka Zuni Lusi Astuti (Universitas Gadjah Mada, 2019)
Macandahan is a grassroot youth community focuses on youth literacy skills improvement. Macandahan interprets the 6 dimensions of literacy as a capital to empower youth to be able to utilize its potential to overcome problems faced by the community. Youth empowerment is not enough to do with literacy and numerical literacy, therefore Macandahan made innovation by doing permaculture farming training through science, digital, financial and cultural literacy. That effort is to address the problem of employment dependency on the oil and gas exploration sector as well as to maintain sustainability of the coconut farming sector. Based on qualitative research data, this article seeks to understand the strategy of Macandahan to empower the youth through literacy from the perspective of Critical Youth Empowerment (CYE). The CYE perspective is used to see the efforts of Macandahan in empowering youth. Macandahan is successful in encouraging young people to learn literacy, facilitating youth to understand the potential and problems by the community, adopting local culture and wisdom in farming, and fostering youth to do networking and advocating themself.